Application of Sustainable Agricultural Technology to Enhance Crop Productivity - milga sari; Parawita Dewanti; Ni Made Ayu Gemuh Rasa Astiti (CV. HEI PUBLISHING INDONESIA, 2024)
Increasing crop productivity is a top priority in supporting global food security amid increasingly complex environmental challenges. Sustainable agricultural technology emerges as a promising approach to enhance agricultural yields without harming the environment. This study aims to explore the application of sustainable agricultural technology in enhancing crop productivity. Through a comprehensive literature review, we identify various sustainable agricultural technologies that can be implemented, such as the use of organic fertilizers, water-efficient irrigation, environmentally friendly pest management, and soil conservation practices. We evaluate the positive impact of each of these technologies on major crop productivity such as wheat, rice, corn, and soybeans. The results of the analysis indicate that the implementation of sustainable agricultural technology effectively enhances crop yields by maintaining ecological balance and reducing negative environmental impacts. The practical implications of this research are that the integration of sustainable agricultural technology into agricultural practices can be an effective solution for improving crop productivity sustainably, while supporting environmental and social sustainability in the long term